Acral lentiginous melanoma—Population, treatment, and survival using the NCDB from 2004 to 2015. (2nd August 2021) - Bian, Shelly X.; Hwang, Lindsay; Hwang, Jennifer; Ragab, Omar; In, Gino K.; Peng, David; Lin, Eugene
Abstract: Acral lentiginous melanoma (ALM) is a rare histological subtype of cutaneous malignant melanoma that typically presents on the palms and soles. To characterize the demographic and treatment characteristics of ALM, we used the National Cancer Database (NCDB) to describe a large multi‐institutional cohort of ALM patients, consisting of 4, 796 ALM patients from 2004 to 2015. ALM was more likely to be diagnosed at a later stage overall compared with non‐ALM cutaneous melanomas, and more likely to be thicker, ulcerated, lymph node positive, and have lymphovascular invasion and positive margins. When stratified by stage, ALM had worse survival compared with non‐ALM patients, most notably in stage III patients with 5‐year survival of 47.5% versus 56.7%, respectively ( p < .001). In ALM patients, older age, male sex, higher comorbidity burden, increased tumor thickness and ulceration, positive lymph nodes, and positive metastasis were independently associated with lower 5‐year survival. Multimodality therapy, defined as surgery in addition to systemic therapy and/or radiation therapy, was associated with higher survival in stage III patients but not in other stages. These results call for further investigation into possible treatment intensification in the ALM population in the future.